The Impact of Curriculum Changes During Each Regime on The Learning Achievement of Junior High School Students in Indonesia - Rieneke Ryke Kalalo; Moh. Nasir; Muhammad; Winda Fashiha; Rachma Putri Kasimbara (Yayasan Inovasi Kemajuan Intelektual, 2025)
The Indonesian education curriculum has undergone dynamic transformations over the course of changing government regimes, from the Old Order era to the Merdeka Curriculum era. This study aims to analyze how changes in curriculum policy in each regime impacted the learning outcomes of junior high school (SMP) students. Using a descriptive qualitative method and a historical literature review, this study examines the shift in curriculum orientation from an ideological to a technocratic-competence orientation. The results of the study indicate that although curriculum changes are intended to respond to the demands of the times and globalization,